2000
DOI: 10.1590/s0034-89102000000100006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da radiosensibilidade ao 60CO do Vibrio cholerae O1 incorporado em ostras

Abstract: Estudo da radiosensibilidade ao 60 Co do Vibrio cholerae O1 incorporado em ostras Radiosensibility of Vibrio cholerae O1 incorporated in oysters, to 60 CO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In this respect, irradiation can be an alternative and appropriate technology to ensure microbiological safety and maintain sensory quality in seafoods. Moraes et al. (2000), using 60 Co ionizing irradiation reported significant reductions in the initial number of V. cholerae in oysters, while Ouattara et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this respect, irradiation can be an alternative and appropriate technology to ensure microbiological safety and maintain sensory quality in seafoods. Moraes et al. (2000), using 60 Co ionizing irradiation reported significant reductions in the initial number of V. cholerae in oysters, while Ouattara et al.…”
Section: Introductionmentioning
confidence: 97%
“…In this respect, irradiation can be an alternative and appropriate technology to ensure microbiological safety and maintain sensory quality in seafoods. Moraes et al (2000), using 60 Co ionizing irradiation reported significant reductions in the initial number of V. cholerae in oysters, while Ouattara et al (2001), using g irradiation in precooked shrimps (Penaeus spp. ), did not observe any adverse effect on sensory parameters (appearance, odor, or taste) in this type of food.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important since the main sources of contamination are environmental degradation and the discharge of domestic sewage, which may cause diseases and compromise oyster growth (Garcia, 2005). Of the animals captured in contaminated environments, bivalve molluscs pose the highest risk to public health because of their filtration ability and bioaccumulation capacity (Suely, Sousa, & Vieira, 2008), with biological agents (bacteria, viruses and parasites) being the main agents carried (Moraes & Jakabi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Para a análise dos resultados, valores extremos são eliminados e os conjuntos de dados são testados quanto à normalidade, utilizando-se em geral o teste de Shapiro-Wilk a 95 % de confiança.Uma vez que o desvio padrão de repetibilidade de um método, s r , está sempre incluído no desvio padrão obtido para análise, a massa mínima de amostra de um MRC, que deve ser utilizada para que as informações de certificação sejam válidas, é aquela em que o desvio padrão relativo (DPR) obtido com determinada massa de amostra se iguala ao s r (ABNT, 2012).Os MRs de origem marinha, entre eles tecido de mexilhão e ostras, são utilizados constantemente em pesquisa aplicada, bem como no biomonitoramento ambiental aquático. Os moluscos bivalves, como mexilhões e ostras são marcadores traços biológicos, são organismos sedentários, estão em contato próximo com a água, alimentam-se por filtração da água e podem vir a acumular em seus tecidos diversos poluentes, isto é, grande quantidade de substâncias químicas, resíduos orgânicos e inorgânicos, e microrganismos presentes na água(GOSLING, 2003).Os agentes que podem ser veiculados são de natureza biológica (bactérias, vírus, parasitas e toxinas de moluscos) e química (elementos tóxicos, resíduos de pesticidas e, mais raramente, antibióticos, quando se trata de cultivo/criação)(MORAES, 2000). Assim, a concentração desses elementos presentes na água e nos tecidos desses organismos, reflete as condições ambientais em que vivem, podendo o seu consumo trazer sérios danos ao organismo humano, representando um risco à saúde pública, uma vez que alguns moluscos chegam a filtrar até 100 litros de água por dia(DAME, 1996).Lamentavelmente, não existem MRs para todas as análises químicas realizadas atualmente em laboratórios.…”
unclassified